Online CME Successful at Improving Awareness, Understanding, and Clinical Use of T2D Treatments - Larkin, Amy (J Endocr Soc, 2021)
We sought to determine if an online continuing medical education (CME) curriculum could improve the clinical knowledge and competence of endocrinologists and primary care physicians (PCPs) related to knowledge and clinical use of GLP-1 RAs. The online CME curriculum consisted of 3 text- or video-based activities focused on practical tips for utilizing GLP-1 RAs in practice, benefits of GLP-1 RAs over therapeutic classes, and knowledge of oral GLP-1 RAs. The educational effects were assessed using a repeated pre-assessment/post-assessment study design. For all questions combined, a chi-squared test assessed whether the mean post‐assessment score differed from the mean pre‐assessment score (absolute changes reported). P values <.05 are statistically significant. The activities launched between June-August, 2019 and outcomes data were collected through November 2019. After being online and accredited for 1 year, the 3 activities have reached over 15,000 clinicians, over 9,500 of which were physicians. Improved knowledge and competence was demonstrated among the target audiences: • 13% increase in endocrinologists (P<.001) and PCPs (P<.001) who effectively utilized a GLP-1 RA in a practical scenario (competence) • 24% increase in endocrinologists (P<.001) and 21% increase in PCPs (P<.001) who identified the impact of GLP-RA therapy on cardiovascular outcomes (knowledge) • 17% increase in endocrinologists (P<.001) and 14% increase in PCPs (P<.001) who correctly identified cardiovascular impact of an emerging GLP-1 RA (knowledge) Persistent knowledge/competence gaps remain: • 9% of endocrinologists and 38% of PCPs need additional education to improve competence related to clinical use of GLP-1s in practice • 64% of endocrinologists and 62% of PCPs need additional education to improve knowledge on the impact of GLP-1 RAs on cardiovascular outcomes • 64% of endocrinologists and 74% of PCPs need additional education to improve knowledge on the cardiovascular impact of emerging GLP-1 RAs This study demonstrates the success of an online curriculum at improving knowledge and competence of endocrinologists and PCPs related to knowledge and clinical use of GLP-1 RAs. Persistent gaps were identified for future educational targets.